First Annual Report of the Bureau of Ethnology : to the Secretary of the Smithsonian Institution 1879-1880, Government Printing Office 1881 - Powell, John Wesley, 1834-1902; Dorsey, James Owen, 1848-1895; Gatschet, Albert S. (Albert Samuel), 1832-1907; Holden, Edward S. (Edward Singleton), 1846-1914; Mallery, Garrick, 1831-1894; Pilling, James Constantine, 1846-1895; Riggs, Stephen Return, 1812-1883; Royce, Charles C., 1845-1923; Yarrow, H. C. (Harry Crécy), 1840-1929 (Salt Lake City, UT : Project Gutenberg, 2010)
"First Annual Report of the Bureau of Ethnology" by John Wesley Powell is a scientific publication written in the late 19th century. This report details the establishment and operations of the Bureau of Ethnology, which focuses on researching and compiling information on North American anthropology, specifically regarding its indigenous peoples. The report covers various studies undertaken during the Bureau's first fiscal year, showcasing significant collaborations and findings in linguistics, cultural customs, and historical accounts. The opening of the report describes the context of its creation, including the transition from previous geological and geographical surveys to the establishment of the Bureau dedicated to ethnological research. It mentions Powell's role as the Director and outlines various methods of operation, highlighting the collaborative nature of the research. Additionally, it references the contributions of numerous scholars and assistants in documenting languages, customs, and social structures among various Native American tribes, setting the stage for the detailed studies that follow in the subsequent sections. (This is an automatically generated summary.)
Report of the Director -- On the evolution of language ... from a study of Indian languages / by J.W. Powell -- Sketch of the mythology of the North American Indians / by J.W. Powell -- Wyandot government: a short study of tribal society / by J.W. Powell -- On limitations to the use of some anthropologic data / by J.W. Powell -- A further contribution to the study of the mortuary customs of the North American Indians / by H.C. Yarrow -- Studies in Central American picture-writing / by Edward S. Holden -- Cessions of land by Indian tribes to the United States: illustrated by those in the State of Indiana / by C.C. Royce -- Sign language among North American Indians compared with that among other peoples and deaf-mutes / by Garrick Mallery -- Catalogue of linguistic manuscripts in the library of the Bureauy of Ethnology / by James C. Pilling -- Illustration of the method of recording Indian languages / from the manuscripts of J.O. Dorsey, A.S. Gatschet, and S.R. Riggs.
Release date is 2010-06-20
Louise Hope, Carlo Traverso, and the Online Distributed Proofreading Team
Keywords: Indians of North America; Indians of North America -- Folklore; Indians of North America -- Government relations; Indians of North America -- Religion; Indian mythology -- North America; Indians of North America -- Funeral customs and rites; Indians of North America -- Languages; Indians of North America -- Land tenure; Indians of Central America -- Languages -- Writing